2015
DOI: 10.1007/s40840-015-0282-2
|View full text |Cite
|
Sign up to set email alerts
|

The k-Metric Dimension of Corona Product Graphs

Abstract: Given a connected simple graph G = (V, E), and a positive integer k, a set S ⊆ V is said to be a k-metric generator for G if and only if for any pair of different vertices u, v ∈ V , there exist at least k vertices w 1 , w 2 , ...,is the length of a shortest path between x and y. A k-metric generator of minimum cardinality in G is called a k-metric basis and its cardinality, the k-metric dimension of G. In this article we study the k-metric dimension of corona product graphs G ⊙ H, where G is a graph of order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 14 publications
0
51
0
Order By: Relevance
“…Our next result on graphs of diameter grater than or equal to six, is a direct consequence of Theorem 26. A fan graph is defined as the join graph K 1 + P n , where P n is a path of order n, and a wheel graph is defined as the join graph K 1 + C n , where C n is a cycle graph of order n. The following closed formulae for the k-metric dimension of fan and wheel graphs were obtained in [4,10]. Since these graphs have diameter two, we express the result in terms of the k-adjacency dimension.…”
Section: The K-adjacency Dimension Of Join Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our next result on graphs of diameter grater than or equal to six, is a direct consequence of Theorem 26. A fan graph is defined as the join graph K 1 + P n , where P n is a path of order n, and a wheel graph is defined as the join graph K 1 + C n , where C n is a cycle graph of order n. The following closed formulae for the k-metric dimension of fan and wheel graphs were obtained in [4,10]. Since these graphs have diameter two, we express the result in terms of the k-adjacency dimension.…”
Section: The K-adjacency Dimension Of Join Graphsmentioning
confidence: 99%
“…The concept of k-metric generator introduced by Estrada-Moreno, Yero and Rodríguez-Velázquez [4,6], is a natural extension of the concept of metric generator. A set S ⊆ V is said to be a k-metric generator for G if and only if any pair of vertices of G is distinguished by at least k elements of S, i.e., for any pair of different vertices u, v ∈ V , there exist at least k vertices w 1 , w 2 , ..., w k ∈ S such that d G (u, w i ) = d G (v, w i ), for every i ∈ {1, ..., k}.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015 Estrada-Moreno et al [1] have found themetric dimension in the path graph, cycle graph, tree graph, and join operation between two graphs. Then in 2016 Estrada-Moreno et al [2] have found -metric dimension on the corona operation between two graphs. In 2017 Geetha and Sooryanarayana [9] have found the -metric dimension in the graph of cartesian product operation results.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Estrada-Moreno et al [4] discovered the k-metric dimension of path graphs, cycle graphs, tree graphs and graphs resulting from joint operations with vertices on each graph are twin vertices. In 2016, Estrada-Moreno et al [5] discovered the kmetric dimension of corona product graphs. In 2017, Geetha and Sooryanarayana [6] discovered the 2-metric dimension of Cartesian product graphs.…”
Section: Introductionmentioning
confidence: 99%